平立两用轧机中离合接手的改进实践 - 王松; 薛林涛 (Jixie chuandong)
Practice and application of clutch of the horizontal and vertical dual mill in the rolling are analyzed,and design flaw,technical adjustment are improved.The cost and the accident rate are reduced.